Comparison of the measurement properties between a short and generic instrument, the 5-level EuroQoL Group's 5-dimension (EQ-5D-5L) questionnaire, and a longer and disease-specific instrument, the Functional Assessment of Cancer Therapy - Breast (FACT-B), in Asian breast cancer patients - Lee, C.F. (2014)
10.1007/s11136-012-0291-7